Potential of Calliandra calothyrsus Leaf Extract to Maintain Estrogen Concentration and Uterine Thickness in Rats - Iriani Setyawati; Ni Nyoman Wirasiti; Luh Putu Eswaryanti Kusuma Yuni (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Calliandra calothyrsus Meissn. leaf extract is potential as phytoestrogens. It influenced male mice reproduction, rat estrous cycle, and ovarian histology in previous study. This research aimed to prove the C. calothyrsus leaf extract potential as phytoestrogen source and the effect on endometrial thickness where the embryo implantation take place in early pregnancy. This study used a Completely Randomized Design used 54 days old female rats (Rattus norvegicus). Rats were divided into K as control group (treated with 0.5% Na-CMC as placebo) and P1, P2, and P3 as three groups with C. calothyrsus leaf extract administration with doses of 17.5; 35; and 70 mg/ kg bw respectively. Treatments were given 1 ml/rat/day orally for 20 days. At day 21st, animals were euthanized to collect blood samples for estrogen hormone analysis. After the dissection, all uterus were collected and weighed. Histological preparation was done with paraffin method and Hematoxylin-Eosin staining. The effective dose was 70 mg/ kg bw that did not decrease the weight of the uterus and the body. This dose even maintained the normal diameter and thickness of uterine walls (endometrium, myometrium, and perimetrium layers) like control rats. The extract in this study could increase estrogen concentration in female rats. This research novelty is that C. calothyrsus leaf extract (70 mg/ kg bw) can be used as an alternative herbal suplement to maintain uterine wall thickness and estrogen concentration in productive women. With further clinical research, this extract is a good candidate as potential estrogen source to overcome women infertility or pregnancy difficulties due to problem of endometrial thickness and lack of endogenous estrogen.